Yersinia enterocolitica exploits different pathways to accomplish adhesion and toxin injection into host cells. (20th March 2015) - Keller, Birgit; Mühlenkamp, Melanie; Deuschle, Eva; Siegfried, Alexandra; Mössner, Sara; Schade, Jessica; Griesinger, Tanja; Katava, Nenad; Braunsdorf, Christina; Fehrenbacher, Birgit; Jiménez‐Soto, Luisa F.; Schaller, Martin; et al.
Summary: The current paradigm suggests that Y ersinia enterocolitica ( Y e ) adheres to host cells via the outer membrane proteins Yersinia adhesin A (YadA) or invasin (Inv) to facilitate injection of Yops by the type III secretion system. In this process Inv binds directly to β1 integrins of host cells while YadA may bind indirectly via extracellular matrix proteins to β1 integrins. Here we challenged this paradigm and investigated the requirements for Yop injection. We demonstrate that Inv‐ but not YadA‐mediated adhesion depends on β1 integrin binding and activation, and that tight adhesion is a prerequisite for Yop injection. By means of novel transgenic cell lines, shRNA approaches and RGD peptides, we found that YadA, in contrast to Inv, may use a broad host cell receptor repertoire for host cell adhesion. In the absence of β1 integrins, YadA mediates Yop injection by interaction with αV integrins in cooperation with yet unknown cofactors expressed by epithelial cells, but not fibroblasts. Electron microscopic and flow chamber studies revealed that a defined intimate contact area between Y e and host cells resulting in adhesion forces resisting shear stress is required for Yop injection. Thus, the indirect binding of YadA to a broad extracellular matrix (ECM) binding host cell receptor repertoire of different cell types makes YadA a versatile tool to ensure Yop injection. In conclusion, given the differential expression of the outer membrane proteins Inv and YadA in the course of Y e infection and differential expression of integrins by various host cell populations, the data demonstrate that Y e is flexibly armed to accomplish Yop injection in different host cell types, a central event in its immune evasion strategy.